Faktor yang Menciptakan Keputusan Pembelian Online pada Bukalapak - Rustanto, Alfonsus Rendy; Octavia, Ayu Nurafni (MBIA, 2024)
The large number of companies offering online sales has resulted in very tight online business competition. Based on the Top Brand Index online buying and selling in 2021-2023, purchases at Bukalapak tended to decline from 9.5% in 2021 to 8.1% in 2022 and even lower to 4.7% in 2023, so that through this study we will analyze the influence of social media, trust and perceived benefits on online purchasing decisions at Bukalapak in Semarang City. The population of this study is consumers who buy products online at Bukalapak. The type of data used is primary data. The data collection method uses a questionnaire. While the analysis technique used is multiple regression analysis. The results of the analysis show that social media has been shown to have a positive and significant effect on purchasing decisions. trust has been shown to have a positive and significant effect on purchasing decisions. perceived benefits have been shown to have a positive and significant effect on purchasing decisions. Based on simultaneous tests, it shows that social media, trust, and perceived benefits have an effect on purchasing decisions together. And the coefficient of determination value shows that the influence of social media, trust, and perceived benefits on purchasing decisions is 75.2% while the remaining 24.8% is influenced by other factors outside this study